Increasing dengue virus vaccine safety and immunogenicity by manipulating antigenic determinants of the flavivirus envelope protein - Hughes, Holly Ruth, author; Blair, Carol D., advisor; Chang, Gwong-Jen J., advisor; Chen, Chaoping, committee member; Bowen, Richard Arnold, committee member (Colorado State University. Libraries, 2010)
Dengue virus (DENV), which exists as four closely related serotypes, is a mosquito-borne pathogen causing significant global disease burden, either as classic dengue fever (DF) or in its most severe manifestation, dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). Severe dengue disease is often associated with secondary DENV infection and hypothesized to frequently be induced by cross-reactive, weakly neutralizing antibodies, a process referred to as antibody-dependent enhancement of infection (ADE). Due to the complex humoral immune response to DENV infection and the complexity of severe DENV disease, currently no licensed DENV vaccine is available. The goal of this dissertation is to increase the safety and immunogenicity of DENV vaccination through a better understanding of the antigenic properties of the envelope protein. To these ends the objectives of this research were to: 1) use site-directed mutagenesis and monoclonal antibody mapping to identify possible cross-reactive epitopes of the DENV-2 E protein which could contribute to ADE (Chapter 2), 2) use B cell epitope modification to construct a serotype-specific DENV-2 vaccine with reduced potential of vaccine-induced ADE (Chapter 3), and 3) identify potential dominant T cell epitopes in West Nile virus E which could act as immunological adjuvants for DENV-2 vaccines (Chapter 4). Humoral immune responses to DENV infection are complex and can exacerbate pathogenicity, yet are essential for immune protection. DENV-2 E protein epitope-specific antigens were created and used to measure immunoglobulin responses to three distinct epitopes in serum samples from DENV-2 infected humans. Immunoglobulin responses to DENV-2 infection exhibited significant levels of individual variation. Antibody populations targeting broadly cross-reactive epitopes centered on the fusion peptide in structural domain II were large, highly variable, and greater in primary than in secondary sera from DENV-2 infected patients, confirming previous studies and identifying the fusion peptide as an immunodominant epitope. E protein domain III cross-reactive immunoglobulin populations were similarly variable and much larger in IgM than in IgG. DENV-2 specific domain III IgG formed a very small proportion of the antibody response, yet was significantly correlated with DENV-2 neutralization, suggesting that the highly protective IgG recognizing this epitope in murine studies plays a role in humans as well. These results begin to tease apart complex humoral immune responses to DENV infection and thus are important for improving our understanding of dengue disease and immunological correlates of protection relevant to DENV vaccine development and testing. DENV vaccines must induce a balanced protective immunity to all four serotypes to reduce the possibility of cross-reactive antibody induced severe disease upon subsequent infection. By modification of immunodominant B cell epitopes of E, cross-reactivity reduced (CRR) DENV-2 DNA vaccine candidates were developed and tested in mice for immunogenicity and potential reductions in developing vaccine induced ADE in mice. Unlike wild-type vaccine, CRR vaccine immunized mouse sera neutralized virus and did not enhance viral infection in vitro. Thus, reducing cross-reactivity in the envelope glycoprotein of DENV may provide a solution to increase vaccine safety and resolve the long-standing obstacle of immune enhancement in dengue vaccine development. DNA vaccination is a highly pursued vaccine platform for its safety, stability, and ease of development, use and manufacturing. However, DNA vaccination is hindered by lower immunogenicity. Methods investigated to increase the immunogenicity of DNA vaccines have included the use of immunological adjuvants; however, few are approved for human use. A dominant, naturally occurring CD4 T cell epitope located in the transmembrane domain of West Nile virus was identified and its ability to increase the immunogenicity of heterologous flavivirus vaccines was investigated. The incorporation of the West Nile virus CD4 epitope into a DENV-2 DNA or protein vaccine significantly increased neutralizing antibody titers compared to parental vaccines without the CD4 epitope. Identifying differential antigenic properties of vaccines may alleviate concerns of imbalanced immunity associated with multivalent vaccinations.
Keywords: monoclonal antibody mapping; dengue virus; antibody dependent enhancement; adjuvant; Dengue viruses -- Prevention; Flaviviruses -- Molecular aspects; Viral vaccines; Antigenic determinants